IMPLEMENTASI PEMBELAJARAN IPA BERDIFERENSIASI DENGAN MODEL PBL UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA SMP DI KEDIRI - Fanani, M. Zainal; Erman; Sulastri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the implementation of differentiated learning using the PBL model and increase the cognitive learning scores of class VII A students at SMP Negeri 1 Grogol Kediri. Quantitative research methods were used in this research with a classroom action research (PTK) approach system which was carried out in 2 cycles where each cycle had 4 levels, including planning, implementation, observation and reflection. The data collection process is carried out through a Posttest at the end of each learning cycle. The results of this research show that the average value of cognitive learning outcomes has increased from 72.94 in the pre-cycle stage to 78.84 in cycle 1, and then to 87.64 in cycle 2. The percentage value of learning completeness has also increased, increasing from 64.7% in the pre-cycle stage to 85.5% in cycle 1 and then to 94.1% in cycle 2. Conclusions from the detailed action assessment (PTK) in class VII A students at SMP Negeri 1 Grogol who applied the PBL model with a Differentiated shows an increase in cognitive scores and the percentage of student learning completeness.